Complementary Description of the Winged Stages of Electrogena braaschi (Ephemeroptera, Heptageniidae) - Godunko, R.J.; Prokopov, G.A.; Kłonowska-Olejnik, M. (Вестник зоологии, 2002)
The male subimago and female imago of Electrogena braaschi (Sowa, 1984) from the central and southern parts of the Crimean Peninsula are described and illustrated. Complementary description of male imago, female subimago and egg is given. Data on the distribution and ecology of the species are provided. Описаны и изображены субимаго самца и имаго самки вида Electrogena braaschi (Sowa, 1984) из центральной и южной частей Крыма. Приводится дополнительное описание имаго самца, субимаго самки и яйца. Представлены сведения по распространению и экологии вида.